2013
DOI: 10.1097/aln.0b013e3182a17e5b
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Blood Flow Increases in Damaged Regions Directly after Acid Aspiration in Rats

Abstract: The data suggest that 10 min after acid aspiration, damaged areas are characterized by increased pulmonary blood flow. The results may impact further treatment strategies, such as drug targeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
7
15
1
Order By: Relevance
“…The latter observation is likely caused by greatly increased pyruvate levels in the hyperperfused lungs as shown in Figures and . This supposition is supported by earlier findings that showed an increased lung permeability index and an increased pulmonary blood flow using PET . Despite significant variability among the cohorts' lactate‐to‐pyruvate ratio trends during injury progression, a combination of the lactate‐to‐pyruvate ratio with lung compliance provides a reliable means to separate the cohorts at the third injection time point.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The latter observation is likely caused by greatly increased pyruvate levels in the hyperperfused lungs as shown in Figures and . This supposition is supported by earlier findings that showed an increased lung permeability index and an increased pulmonary blood flow using PET . Despite significant variability among the cohorts' lactate‐to‐pyruvate ratio trends during injury progression, a combination of the lactate‐to‐pyruvate ratio with lung compliance provides a reliable means to separate the cohorts at the third injection time point.…”
Section: Discussionsupporting
confidence: 66%
“…To explain this discrepancy, we postulate that locally increased pyruvate concentration, rather than decreased lactate production, was responsible for the low lactate‐to‐pyruvate in severely injured rats. The increased pyruvate concentration is caused by the retention of hyperpolarized pyruvate in the extracellular space of edematous lungs .…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the hemodynamic changes observed in the regional pulmonary artery during lung consolidation are complex. However, this phenomenon was consistent with the increased pulmonary blood flow observed in the damaged regions of an ARDS rat model induced directly by acid aspiration because the relaxing factors released from the damaged alveoli limit hypoxic pulmonary vasoconstriction [5759]. …”
Section: Introductionsupporting
confidence: 70%
“…However, it has been shown that pulmonary blood flow increases significantly following acute lung injury [32], and in hyperpolarized pyruvate experiments performed by our group (data not shown) significantly increased pyruvate signal in uninjured regions of the lung was observed following acute injury to other parts of the lung. Given these observations, we believe that significantly higher hyperpolarized signal should be present in all regions of the lungs despite the injury being heterogeneously distributed.…”
Section: Discussionmentioning
confidence: 56%